Dzieci umarłych Elfriede Jelinek w pułapce marketingu. Poznawcze i pragmatyczne aspekty przekładu / Elfriede Jelinek’s Die Kinder der Toten (The Children of the Dead) entrapped by book marketing Cognitive and pragmatic facets of translation - Majkiewicz, Anna (Przekłady Literatur Słowiańskich, 2019)
This article attempts to answer the question: why the Polish translation of a novel by Elfriede Jelinek The Children of the Dead (Die Kinder der Toten) did not stir any debate in the circles of literary criticism in Poland. While analysing the actions carried out as a part of the W.A.B.’s (a Warsaw-based publishing house) strategy to advance the publication process and to popularize Jelinek’s oeuvre, we may notice that they actually confirm the publisher’s endeavour to balance economic and symbolic capital (Bourdieu). It allows us to reconstruct the “marketing” aims of the translation in question. Yet both the cognitive and pragmatic facet of the Austrian Nobel Laureate’s Polish translation remain to be reconstructed by the readers.